Charting the course to cleaner shipping routes: emission inventory for Baltic Sea shipping and green fuel potential - Rohan Kumar; Kent Salo; Fabien Yao; Sebe Maxime; Recuero Vitro Laura; Dennis Booge; Christa A. Marandino; Shams Al-Hajjaji; Nele Matz-Luck; Anna Rutgersson (Carbon Management)
This study presents a high-resolution shipping emission inventory for the Baltic Sea, assessing the environmental impacts of four fuel-based scenarios under a projected threefold increase in gross tonnage by 2050. The study evaluates how regulatory changes and alternative fuels, such as hydrogen and ammonia, can reduce emissions and advance sustainability in shipping. The study uses a bottom-up approach, combining activity data, fuel data, and emission factors to estimate tank-to-wake emissions. Comparative analysis indicates improved emissions prediction across all pollutants. While use of liquefied natural gas (LNG) and scrubber-equipped ships reduce sulphur oxides (SOx) emissions, they incur notable environmental trade-offs. By 2050, significant reductions in particulate matter (99%) and carbon dioxide are projected, while SOx emissions are expected to approach zero using hydrogen, ammonia, and methanol fuels. These reductions are helped by the decline in traditional fuels and technological progress. The current transition to cleaner marine fuels is insufficient to meet the IMO’s 2030 and 2050 carbon reduction targets. While tank-to-wake contributes significantly toward emissions reduction, a broader focus on the well-to-wake approach is also critical for achieving net-zero emissions by 2050. Policy efforts should accelerate the adoption of green fuels and address challenges such as methane slip from LNG-powered ships.